ANALISIS JALUR PENGARUH PRODUK DAN HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUTUSAN PEMBELIAN KOPI DI KAB. JOMBANG : Studi Kasus: Coffee Shop Konoa - Qomariah, Siti Nur; Shodiq, Ja’far; Choir, Rismainuri Ummu (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Consumer devotion is the yardstick by which businesses in the real world judge their performance. The amount of revenue is thought to be primarily determined by customer loyalty. The product and price are also a factor in determining consumer buying choices. Through the district's coffee buying choices, this research seeks to map out the impact of product and price on customer loyalty. partly or concurrently, jombang. collected through surveys or forms for research (primary data). All randomly chosen Konoa coffee store patrons made up the study's sample. While using a random sampling method to determine the group. Multiple linear regression analysis, t, f, path, and determination tests are the types of analysis that were used. The tests carried out revealed that the Konoa coffee shop's purchasing choices were not greatly impacted by the findings of the product study. The Konoa coffee shop's customers' buying choices are heavily influenced by price. The product has no discernible impact on repeat business at Konoa Coffee. At the Konoa coffee store, price has a big impact on customer devotion. Customer devotion at Konoa Coffee Shop is significantly influenced by purchasing choices. Making purchases can mediate how goods affect customer allegiance to Kona Coffee store patrons. The impact of price on customer loyalty to Konoa coffee store patrons can be moderated by purchasing choices